ANALISIS PERMINTAAN TELUR AYAM DI PROVINSI ACEH - Fittresdy Isman, Abubakar Hamzah, Raja Masbar. (Jurnal Ilmu Ekonomi : Program Pascasarjana Unsyiah, 2014)
Abstract : The purpose of this study was to determine the effect of chicken egg prices, the price of substitutes, income, and number of residents to the demand of chicken eggs in the province of Aceh. The analysis used is the Multiple Linear Regression Analysis (multiple regressions). The type of data used in this study is secondary data preformance form (time series) from 1980 to 2011, covering the variable per capita income, the price of chicken eggs, duck eggs price, number of population and demand for chicken eggs obtained from relevant agencies such as : Central Bureau of Statistics (BPS), the Office of Trade and Industry, and other offices as well as from a variety of sources and other literature related to this study. Based on the estimation, the variables negatively affect the price, and the price of duck eggs, income, and population positive effect on demand for chicken eggs in the province of Aceh. Variations in the demand for chicken eggs Aceh province can be explained by variations in the price of chicken eggs, duck eggs prices, population, and income of 94.0 percent, and the remaining 6.0 percent are influenced by other variables, such as: taste, style, and the distribution of income in society and others. Either simultaneously or partially, the price of chicken eggs, duck eggs prices, income, and population significantly influence the demand for chicken eggs in the Province of Aceh.The results showed that the income is the dominant factor affecting the demand for chicken eggs in the province of Aceh, therefore an increase in supply of chicken eggs in the province of Aceh to be seen by its association with the Gross Regional Domestic Product (GDRP) increasing Aceh province. Keywords : Chicken Egg Demand. Abstrak : Tujuan penelitian ini adalah untuk mengetahui pengaruh harga telur ayam, harga pengganti, pendapatan dan jumlah penduduk terhadap permintaan telur ayam di Provinsi Aceh. Analisisnya menggunakan analisis regresi linear berganda (Multiple Regressions).Jenis data yang dipergunakan dalam penelitian ini adalah data sekunder dalam bentuk (Time Series) dari tahun 1980 sampai dengan tahun 2011, meliputi variabel pendapatan per kapita, harga telur ayam, harga telur bebek, kemudian jumlah penduduk dan permintaan telur ayam yang diperoleh dari instansi terkait seperti, Badan Pusat Statistik (BPS), Kantor perdagangan dan perindustrian dan kantor – kantor lainnya serta dari berbagai sumber dan literatur lain yang ada kaitannya dengan penelitian ini. Berdasarkan hasil estimasi variabel harga berpengaruh negatif dan harga telur itik, pendapatan dan jumlah penduduk berpengaruh positif terhadap permintaan telur ayam di Provinsi Aceh. Variasi permintaan telur ayam di Provinsi Aceh dapat dijelaskan oleh variasi harga telur ayam, harga telur itik, jumlah penduduk dan pendapatan sebesar 94,0 persen dan sisanya sebesar 6 persen dipengaruhi oleh variabel lainnya seperti selera, corak dan distribusi pendapatan dalam masyarakat dan lain-lain. Baik secara simultan maupun secara parsial harga telur ayam, telur itik, pendapatan dan jumlah penduduk berpengaruh signifikan terhadap permintaan telur ayam di Provinsi Aceh. Hasil penelitian menunjukkan bahwa pendapatan faktor dominan yang mempengaruhi permintaan telur ayam di Provinsi Aceh, oleh karenanya peningkatan persediaan telur ayam di Provinsi Aceh harus dilihat dengan keterkaitanya dengan PDRB Provinsi Aceh yang semakin meningkat. Kata Kunci : Permintaan Telur Ayam.